The social impact of the Persians in the first Abbasid era - العوكي رشا; وفاء صارم; راميا جامع (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
The research deals with the role of the Persians in social life in the Abbasid era. Abbasid society was a mixture of races that included Arabs, Turks, and Persians, who played a major role in the success of the Abbasid call. This allowed them to enjoy positions that were reserved for Arabs only before, whether at the state level or At the level of society with its various facilities, and sometimes they aspired to more than that, and the contact of the Abbasids with the Persians resulted in customs and traditions that included various aspects of social life, such as food, clothing, and drink, Even in the Persian holidays, they recognized them, such as Nowruz and the festival, and the matter developed until the most correct caliphs celebrated these holidays. All of this led to an increase in the influence of the Persians in Abbasid society. The role of the Persians in the establishment of the Abbasid state was clarified, as the Khorasan origin of the Abbasid call and their support for it was accomplished. As a result of the friction between the Persians and the Arabs, the Arabs took away from them aspects of amusement, namely games, singing gatherings, manifestations of pomp and greatness, and others that were studied. The Persian influence was also clearly evident in social customs such as veiling, the colors of food, clothing and adornment traditions, and palace construction. The choice of this research stems from the fact that political studies have received considerable attention without delving into social conditions, in order to highlight some of the positive and negative aspects of Persian influence. The social life during the Abbasid era, which is the focus of this study, underwent significant transformations that affected various social aspects due to the substantial Persian influence and the esteemed position the Persians held among the Abbasid caliphs.